Efficacy and safety of probiotics in the treatment of irritable bowel syndrome: A systematic review and meta-analysis of randomised clinical trials using ROME IV criteria. Issue 5 (May 2023) - Konstantis, Georgios; Efstathiou, Stylianos; Pourzitaki, Chryssa; Kitsikidou, Elisavet; Germanidis, Georgios; Chourdakis, Michail
Summary: Background: Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disorder which affects a great number of patients globally. Clinical trials and meta-analyses have evaluated different therapies for IBS. Some of them have shown that probiotics play a significant role in the management of IBS-patients. Nevertheless, results are controversial, and the efficacy of the administration of probiotics remains to be confirmed, especially in regard to which type of probiotic-strains are beneficial. Aim: The aim of the present meta-analysis is to assess the efficacy and safety of the administration of probiotics to IBS-patients with a diagnosis based on Rome IV criteria, which is performed for the first time. Methods: Electronic databases (Pubmed, Scopus and Cochrane) were searched until 26.01.2023 for randomized controlled trials (RCTs) studying the administration of probiotics in adult IBS-patients, who were categorized according to the Rome IV criteria. The risk of bias was assessed using the Cochrane Risk of Bias tool (ROB) 2.0. Weighted and standardized mean difference with the 95% confidence intervals were used for the synthesis of the results. Primary outcomes were the decrease of IBS-Symptom Severity Score (IBS-SSS) and decrease of abdominal pain. The secondary outcomes were the improvement in quality of life (QoL) and the decrease of bloating. Lastly, the adverse effects of probiotics were evaluated. The protocol of the study has been registered at protocols.io (DOI dx.doi.org/10.17504/protocols.io.14egn218yg5d/v1). Results: Six double-blind (N = 970) placebo-control RCTs fulfilled the inclusion criteria and overall, nine different strains of probiotics were examined. No significant reduction in IBS-SSS (WMD −43.2, 95% CI −87.5 to 1.0, I 2  = 82.9%) was demonstrated, whereas a significant decrease regarding abdominal pain (SMD −0.94, 95% CI −1.53 to −0.35, I 2  = 92, 2) was shown. Furthermore, no correlation between improvement of QoL and the use of probiotics (SMD −0.64, 95% CI −1.27 to 0.00, I 2  = 93, 9%) was shown. However, probiotics were associated with a significant reduction in bloating (SMD −0.28, 95% CI −0.47 to −0.09, I 2  = 36, 0%). A qualitative synthesis was conducted about adverse events and showed that the use of probiotics' is safe without severe adverse events. Conclusions: The administration of probiotics to IBS-patients demonstrated a positive effect on pain and bloating, but due to significant heterogeneity and confounding factors, that were not examined in the included studies, a definitive statement cannot be made. Moreover, probiotics did not lead to an improvement in other parameters. There is a need for larger RCTs in IBS-patients diagnosed according to Rome IV (not III) criteria and especially it is essential to be conducted RCTs which examine the administration of specific strains and have similar methodological characteristics.